An examination of recreational divers' underwater behaviour by attitude–behaviour theories - Ong, T.F.; Musa, G. (Taylor & Francis (Routledge), 2011)
The increasing demand for dive tourism activities has resulted in concerns over scuba divers' incremental impacts on the underwater marine environment. Hence, there is a need to better understand the antecedents of scuba divers' underwater behaviour. This study applied theory of planned behaviour (TPB) and norm activation theory (NAT) of altruistic behaviour in examining the relationship between diving attitude, perceived behavioural control, subjective norms and personal norms (PNs) with responsible underwater behaviour among scuba divers. Using the combination of purposeful and convenience samplings, data were collected from divers (N = 413) who visited the top five most attractive islands in Malaysia. The results supported the use of TPB as a basis for explaining the underwater behaviour of divers. Among the four constructs examined, attitude and PNs were found to be of paramount importance in influencing pro-environmental behaviour. This study also validated the exploratory dimensions that constitute the measurement constructs for scuba diving attitude and responsible underwater behaviour. Scuba diving stakeholders should emphasise continuous education and an integrated programme of marine conservation to enhance divers' attitude and personal commitment towards pro-environmental behaviour. These are crucial for the sustainability of the scuba diving industry.